Effect of smoking, alcohol, and other factors on the selenium status of a healthy population. Issue 3 (September 1983) - Lloyd, B; Lloyd, R S; Clayton, B E
Abstract : In a study of selenium status in 391 apparently healthy subjects resident in the south of England statistical examination of the data showed a significant effect with regard to age, smoking, alcohol, and oral contraceptives. The most important of these factors seems to be a combination of alcohol and smoking habits in men over 30. Reference ranges have been established for glutathione peroxidase activities and the concentrations of selenium in whole blood plasma and erythrocytes.